A radical plan for the English language : Thomas Spence’s "New Alphabet" - Joan Beal (Miranda: Revue Pluridisciplinaire du Monde Anglophone, 2016)
This article discusses Thomas Spence’s scheme of reformed spelling and its place within Spence’s broader plan for the reform of society. Whilst earlier commentators on and biographers of Spence tended to dismiss his ideas on language as trivial or even misguided, more recent scholarship recognises the interconnection of language and politics in Spence’s radical plan. This article sets Spence’s linguistic ideas within the context of 18th-century prescriptivism and standardisation of language, arguing that, although Spence is prescriptive in advocating the adoption of “correct” pronunciation, his plans for spelling reform are in direct opposition to the prevailing trends of the time. Spence’s ideas on spelling reform both hark back to those of 16th-century reformers (e.g. Hart), and anticipate 20th-century schemes such as the Initial Teaching Alphabet, but his scheme for implementing them is unique. Finally, the article resumes its discussion of the interconnectedness of language and politics, setting Spence’s ideas alongside those of later scholars and activists such as Cobbett and Foucault.